Estimating the economic cost of disability in Ireland - John Cullinan; Brenda Gannon; Seán Lyons (The Economic and Social Research Institute (ESRI), 2008)
Addressing the extra economic costs of disability seems a logical step towards alleviating elements of social exclusion for people with disabilities. This paper estimates the economic cost of disability in Ireland in terms of the additional spending needs that arise due to disability. It defines and estimates models of the private costs borne by families with individuals who have a disability in Ireland when compared to the wider population, both in general and by severity of illness. Our modelling framework is based on the standard of living approach to estimating the cost of disability. We extend on previous research by applying an ordered logit modelling approach to Living in Ireland survey data 1995-2001 to quantify the extra costs of living associated with disability in Ireland. We also derive estimates of the cost of disability for 'pensioner' and 'non-pensioner' households, as well as over time. Our findings suggest that the economic cost of disability in Ireland is large, varies by severity of disability, and across household types. Overall our findings have important implications for measures of poverty in Ireland.
Keywords: 330; Behinderte; Kosten; Privater Haushalt; Lebensstandard; Schätzung; Irland